Multiple cause-of-death data among people with AIDS in Italy: a nationwide cross-sectional study - Enrico Grande; Antonella Zucchetto; Barbara Suligoi; Francesco Grippo; Marilena Pappagallo; Saverio Virdone; Laura Camoni; Martina Taborelli; Vincenza Regine; Diego Serraino; Luisa Frova (BMC, 2017)
Abstract Background Multiple cause-of-death (MCOD) data allow analyzing the contribution to mortality of conditions reported on the death certificate that are not selected as the underlying cause of death. Using MCOD data, this study aimed to fully describe the cause-specific mortality of people with AIDS (PWA) compared to people without AIDS. Methods We conducted a nationwide investigation based on death certificates of 2,515 Italian PWA and 123,224 people without AIDS who had died between 2006 and 2010. The conditions most frequently associated with PWA mortality, compared to people without AIDS, were identified using an age-standardized proportion ratio (ASPR) calculated as the ratio between the age-standardized proportion of a specific cause among PWA and the same proportion among people without AIDS. Results The most frequently reported conditions at death among PWA were infectious/parasitic diseases (52%), digestive (36%), respiratory (33%), and circulatory (32%) system diseases, and neoplasms (29%). All AIDS-defining conditions resulted highly associated (ASPR significantly greater than unity) with PWA deaths. Significant associations also emerged for leishmaniasis (ASPR = 188.0), encephalitis/myelitis/encephalomyelitis (ASPR = 14.3), dementia (ASPR = 13.1), chronic viral hepatitis (ASPR = 13.1), liver fibrosis/cirrhosis (ASPR = 4.4), pneumonia (ASPR = 4.4), anal (ASPR = 12.1) and liver (ASPR = 1.9) cancers, and Hodgkin's disease (ASPR = 3.1). Conclusions Study findings identified the contribution of several non-AIDS-defining conditions on PWA mortality, emphasizing the need of preventive public health interventions targeting this population.